A Study on Providing Children in the Preschool Environment the Opportunity to Express Themselves - (:unkn) unknown (University of Jaffna, 2012)
This study focuses on providing children in the preschool environment the opportunity to express themselves. The foundation of early childhood education is essential for the preparation of individual’s whole life. The richer the child’s language, the better is one’s prospect of fitting into and progressing effectively in the early school years. The teacher’s role is vital and important and should support children to develop their cognitive, intellectual, social, and emotional development at the beginning. But direct observation proved that most teachers are not concerned nor do they give children the opportunity express their own experience’s in the classroom. As a result it would have an effect on the development of the child’s abilities. Therefore, this study attempts to investigate how the child expresses itself in the preschool context. The survey method was used as the research design and interviews and observations were used as data collection methods. According to the findings positive factors as well as negative factors could be identified. Preschools are concerned to provide the opportunity of expressing their ideas in various ways, such as general conversation, pictures descriptions, songs and poems, play activities, drawing, describing daily experiences, storytelling and simple text books. Some teachers were not adequate the subject knowledge to motivate children to self-expression. Some teachers failed to provide the children opportunity for self-express when involved in activities. A few teachers encourage children with the potential to express themselves at certain level. A few teachers had the concern to encourage children to express themselves freely
Keywords: Child’s personality; Preschool education; Preschool environment,; Types of play